2022
DOI: 10.1093/bjd/ljac018
|View full text |Cite
|
Sign up to set email alerts
|

Pain experiences among those living with hidradenitis suppurativa: a qualitative study

Abstract: Background Pain is rated by patients with hidradenitis suppurativa (HS) as the disease’s most impactful symptom. HS therapies are often insufficient to control inflammatory disease activity and pain. A better understanding of patient experiences with pain may improve patient–provider relationships and help identify strategies for addressing HS pain. Objectives This qualitative study sought to characterize lived pain experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A recent systematic review of the qualitative literature on experiences of individuals with HS identified a recurring theme of health care failing to meet patients’ needs and expectations. The study’s reported themes of stigmatization and limited access to HS specialty care were also identified in our larger qualitative studies on pain and access to health care in HS. Howell et al highlighted patients’ feelings of inadequate support from their physicians in their HS management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of the qualitative literature on experiences of individuals with HS identified a recurring theme of health care failing to meet patients’ needs and expectations. The study’s reported themes of stigmatization and limited access to HS specialty care were also identified in our larger qualitative studies on pain and access to health care in HS. Howell et al highlighted patients’ feelings of inadequate support from their physicians in their HS management.…”
Section: Discussionmentioning
confidence: 99%
“…Low prescription rates of these agents reflect potential undertreatment of HS, risking disease progression and morbidity. Poor disease control can also lead to an increased need for analgesic medications and searches for alternative pain relief strategies …”
Section: Introductionmentioning
confidence: 99%
“…In HS, black race has been associated with diagnostic delay, increased disease severity, lower access to dermatologic specialty care, and increased healthcare utilization [28][29][30]. A qualitative study also suggested perceived stigma from providers led patients to feel hesitant seeking care for their pain and contributed to undertreatment, especially during acute flares [16]. The complex interplay of systemic, patient, and provider factors continues to sustain health disparities experienced by black patients, highlighting the need for comprehensive approaches to address HS pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Patients living with HS have 1.3-4.8 times higher odds of depression compared to control populations [11][12][13][14]. The painful abscesses and unpredictable flares may limit daily activities in patients with HS and can lead to feelings of hopelessness and social isolation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal recording of clinical outcomes may also support analyses of treatment effectiveness, which offers insight into treatment effect in the broader HS population that clinical trial data cannot provide . Further integration of patient-reported measures allows capture of treatment effect on symptoms and life quality, which patients may hesitate to discuss due to fear of stigmatization and which may otherwise be underestimated by clinicians . The objective of this study was to provide expert and patient consensus-based recommendations on the application of validated, HS-specific outcome measures that are feasible for clinical practice.…”
Section: Introductionmentioning
confidence: 99%